Cross-cultural undergraduate internships : a toolkit for empowering the next generation - Gennaro, Davide de (Emerald Publishing Limited, 2023)
Life-defining experiential learning opportunities, especially international ones, do not "just happen": they are carefully and purposefully designed. Responding to the needs of institutions, businesses, and non-profits, Cross-Cultural Undergraduate Internships provides the critical know-how for designing, measuring, and assessing roles that can kickstart student growth and empowerment. Featuring the SantAnna Institute, an Italian educational organization that offers study abroad programs in partnership with American universities, as a core case study, chapters showcase lived experiences to identify the characteristics that make an undergraduate cross-cultural internship useful for the development of both the individual and the organization. Advising on logistical considerations such as renumeration, evaluation, and duration, as well as exploring the broader impact and effectiveness of such programs, the authors propose a toolkit for institutions and organizations to design and evaluate undergraduate internships with a global reach that is in line with new needs in the world of work. A breakthrough text for designing a complete and formative internship experience and for coaching students to consciously engage in intercultural environments, Cross-Cultural Undergraduate Internships provides a roadmap for crafting effective learning experiences that will shape the next generation of scholars, activists, and professionals.
Keywords: Internship programs.; Multicultural education -- Study and teaching (Internship); Education -- Counseling / Career Development.; Industrial or vocational training.; elektronické knihy; electronic books